Use of Subfluvial Optical Cable in a Region Without Land-Based Infrastructure – a Project to Deploy Advanced Communications in the Amazon Region - Grizendi, Eduardo; Stanton, Michael (My University, 2013)
For several years, terrestrial optical cable has been deployed along highways, railways and electric power transmission lines. These land routes have been used to support national and regional backbones of telecommunications networks, in particular, Internet backbones. To complement these, there is massive use of submarine optical cables for intercontinental connection of national telecommunications networks, giving them worldwide reach. However, in many countries, there are still regions where no such land routes exist, notably in areas of difficult access by land and of low population density. Some of these regions have, in the rivers that traverse them, a common solution to meet diverse society needs. One of them is the Amazon region of Northern Brazil and some neighboring countries, where there are few roads serving the main cities and where the population lives mainly along the banks of the great rivers that cross it. This paper aims to highlight the alternative of deployment of optical routes along riverbeds in regions where there are few or no roads, railways or even electric power transmission lines, and to present a Brazilian project, still in its early stages, of the deployment of a set of optical cables along the courses of its major rivers - the Amazon, Negro and Solimões. It is hoped that this approach may serve as an example for large river basins in other continents with difficult land based access.
Keywords: Subfluvial optical cable; Amazon region; Brazilian Broadband Plan; alternative of deployment of optical routes in Amazon region